Epidemic Spread and Its Management Through Governance and Leadership Response Influencing the Arising Challenges Around COVID-19 in Pakistan—A Lesson Learnt for Low Income Countries With Limited Resource - Nawaz, Ahsan; Su, Xing; Barkat, Muhammad Qasim; Asghar, Sana; Asad, Ali; Basit, Farwa; Iqbal, Shahid; Zahoor, Hafiz; Raheel Shah, Syyed Adnan (Frontiers in Public Health, 2020)
The coronavirus disease (COVID-19) was first reported in China (Wuhan) at the end of 2019. It has rapidly spread over 216 countries, including the USA, UK, Europe, Russia, and many Asian countries. It has affected more than 4.5 million people, and around 0.3 million deaths have been reported globally. Many preventive measures have been adopted worldwide to mitigate its spread. The government of Pakistan has also taken many preventive measures to combat the COVID-19 outbreak, such as rapid response by governance, continuous monitoring of the pandemic spread in the affected areas, and integration of resources from multiple sectors, including health, education, defense, and media. According to global statistics, the number of COVID-19 cases in the country remained remarkably lower than the expected number for the first 169 days, as compared to other countries. A total of 286,674 confirmed cases, including 16,475 active, 6,139 deaths, and 264,060 (92%) recoveries were reported. The study finds that strict adherence to national policies, effective governance, and unity at the national level resulted in better outcomes. Hence, the preventive measures, rapid responses, and strategies adopted for combating the challenges could be adopted as a learning tool for other countries having similar work environments and financial constraints. This paper can help and guide governance/public actions in response to the possible rebound of coronavirus this fall/winter.